PERAN PENYULUH PERTANIAN DALAM MENDUKUNG KETAHANAN PANGAN PADA MASA PANDEMI COVID-19 DI KOTA TARAKAN - Zulhafandi Zulhafandi; Ahmad Mubarak (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2021)
AbstractExtension agents are promoters in influencing the innovation adoption process before the innovation is adopted by the community. In addition, extension workers are able to build farmer skills, strengthen farmer institutions, and increase partnerships with the government and other agribusiness actors in supporting food security. Among the roles of the extension agent are as an advisor to the organizer, technical assistant and as a liaison. North Kalimantan is a province that directly borders with neighboring countries forcing the government to be aware of the spread of this epidemic by implementing all the appeals from the central government, including several cities/districts that have implemented PSBB. This condition is clearly not profitable for the community, especially farmers, fishermen and ranchers who have difficulty in meeting the needs of themselves and their families. Coupled with the extension workers who spearhead agricultural development, who help, facilitate farmers in their farming activities must also follow the appeals and rules from the government. So that the interaction between extension workers and farmers is very limited and interferes with the extension agenda that had previously been prepared by the extension workers with the farmers. The purpose of this study is to identify and describe the role of agricultural extension workers in supporting food security during the Covid-19 pandemic in Tarakan City. This study uses a descriptive method with a qualitative approach. Data collection techniques in a qualitative approach are carried out with in-depth observations, data analysis begins by examining all data collected through in-depth interviews with key informants from agricultural extension workers and main actors in the agricultural sector. The technique of checking the validity of the data (data validity) in this study is the triangulation technique. Based on the analysis of the role of agricultural instructors, it was found that there were obstacles or obstacles in carrying out extension activities and implementing the role of extension workers due to the limited intensity of face-to-face meetings with fostered farmers. Of the four roles of agricultural instructors, extension workers have more roles in the category as advisors and technical assistance in agricultural cultivation, but the role as organizer is not optimal because it can be seen from the managerial and administrative abilities of farmers who have not been good, besides that the role as a liaison has also not worked well. this can be seen from the lack of facilitation of farmers with financial institutions and marketing institutions.Key words: The Role of Extension, Food Security, Covid-19AbstrakPenyuluh merupakan promotor dalam mempengaruhi proses adopsi inovasi sebelum inovasi diadopsi oleh masyarakat. Selain itu, penyuluh mampu membangun keterampilan petani, memperkuat kelembagaan petani, serta meningkatkan kemitraan dengan pemerintah dan pelaku agribisnis lainnya dalam mendukung ketahanan pangan. Diantara peran penyuluh adalah sebagai penasehat organisator, pendamping teknis dan sebagai penghubung. Kalimantan Utara merupakan propinsi yang berbatasan langsung dengan Negara tetangga memaksa pemerintahnya mewaspadai penyebaran wabah ini dengan menerapkan segala himbauan dari pemerintah pusat termasuk beberapa kota/kabupaten yang telah menerapkan PSBB. Kondisi ini jelas tidak menguntungkan bagi masyarakat terutama petani, nelayan dan peternak yang kesulitan dalam memenuhi kebutuhan diri dan keluarganya. Ditambah lagi dengan penyuluh yang menjadi ujung tombak pembangunan pertanian, yang membantu, memfasilitasi petani dalam kegiatan usahataninya juga harus mengikuti himbauan dan aturan dari pemerintah. Sehingga interaksi penyuluh dan petani sangat terbatas dan mengganggu agenda penyuluhan yang sebelumnya sudah disusun penyuluh bersama petani. Tujuan dari penelitian ini adalah Mengetahui dan mendeskripsikan Peran Penyuluh Pertanian Dalam Mendukung Ketahanan Pangan Pada Masa Pandemi Covid-19 Di Kota Tarakan. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dalam pendekatan kualitatif dilakukan dengan Observasi mendalam, analisis data dimulai dengan menelaah seluruh data yang dihimpun melalui wawancara mendalam dengan key informan dari penyuluh pertanian dan pelaku utama dalam sektor pertanian. Teknik pemeriksaan keabsahan data (validitas data) dalam penelitian ini adalah teknik triangulasi. Berdasarkan analisis peran penyuluh pertanian ditemukan terdapat hambatan atau kendala dalam melaksanakan kegiatan penyuluhan dan pelaksanaan peran penyuluh dikarenakan terbatasnya intensitas pertemuan tatap muka dengan petani binaan. Dari ke empat peran penyuluh pertanian, Penyuluh lebih berperan dalam kategori sebagai penasehat dan pendampingan teknis budidaya pertanian, namun untuk peran sebagai organisator belum optimal karena terlihat dari kemampuan manajerial dan administrasi petani yang belum baik, selain itu peran sebagai penghubung juga belum berjalan dengan baik, hal ini terlihat dari belum terfasilitasinya petani dengan lembaga pembiayaan dan lembaga pemasaran.Kata kunci: Peran Penyuluh, Ketahanan Pangan, Covid-19